Executive compensation and firm performance in Chinese state-owned enterprises and private firms - Xu, Weixiao (2022)
The extremely high level of executive remuneration of listed companies has sparked global concern and the sheer scale of executive remuneration of listed companies in China has also been questioned by many people. Based on the agency theory, for the period 2010-2020, this study investigates the link between cash and non-cash CEO remuneration and firm performance in state-owned enterprises (SOEs), private enterprises, and all A-share listed companies in China. We collected 4,660 Chinese listed companies from the CSMAR database and used a quantitative research method and construct OLS regression models to test and analyse the association between senior management compensation and company performance. In both Chinese SOEs and private enterprises, the findings demonstrate a highly favourable association between cash and non-cash pay and company performance. Furthermore, we also suggest that cash remuneration is more linked to company performance in SOEs and non-cash compensation is more connected with firm performance in private firms. Additionally, the relationship between both cash compensation and non-cash compensation with firm performance is stronger in private companies. With the findings, our research has implications for the construction of a reasonable remuneration system for listed companies in China, particularly SOEs.